A TWITTER-INTEGRATED WEB SYSTEM TO AGGREGATE AND PROCESS EMERGENCY-RELATED DATA - YONG , CHANG YI (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
A major challenge when encountering time-sensitive, information critical emergencies is to source raw volunteered data from on-site public sources and extract information which can enhance awareness on the emergency itself from a geographical context. This research explores the use of Twitter in the emergency domain by developing a Twitter-integrated web system capable of aggregating and processing emergency-related tweet data. The objectives of the project are to collect volunteered tweet data on emergencies by public citizen sources via the Twitter API, process the data based on geo-location information and syntax into organized informational entities relevant to an emergency, and subsequently deliver the information on a map-like interface. The web system framework is targeted for use by organizations which seek to transform volunteered emergency-related data available on the Twitter platform into timely, useful emergency alerts which can enhance situational awareness, and is intended to be accessible to the public through a user-friendly web interface. Rapid Application Development (RAD) is the methodology of choice for project development. The developed system has a system usability scale score of 84.25, after results were tabulated from a usability survey on 20 respondents. Said system is best for use in emergencies where the transmission timely, quantitative data is of paramount importance, and is a useful framework on extracting and displaying useful emergency alerts with a geographical perspective based on volunteered citizen Tweets. It is hoped that the project can ultimately contribute to the existing domain of knowledge on social media-assisted emergency applications.